Wyzwania edukacji (w Polsce) z perspektywy psychologicznej - Cyzio, Dominika (Hybris, 2017)
The aim of this paper is to look at the issues concerning the challenges of the modern education system, including the situation in Poland. It cannot be denied that institutionalized education is imperfect and does not develop human’s full potential. It even turns out that the current education system can be harmful to natural child’s development: it can limit child’s abilities and personal resources. Conditions of present education system are based on wrong assumptions, which contradict the psychological theories including learning processes, practicing creative thinking, intellectual, emotional and social development, and many others. All this contributes to the transfer of knowledge largely useless in everyday life or downplaying the uniqueness of the individual. It prevents learning how to flexibly adapt to the dynamic life conditions. Chances to cope with these serious challenges are various forms of alternative education that take into account the natural human development and psychological functioning.